Pelatihan Kebersyukuran untuk Meningkatkan Sense of School Belonging Siswa SMP - Indah Nadzifah Hayati; Budi Andayani (Faculty of Psychology, Universitas Gadjah Mada, 2016)
Sense of School Belonging (SoSB) is a major requirement for students to function optimally at school. This study examined the effect of gratitude training on SoSB of Junior High School students. This study used a quasi-experimental untreated control group design with dependent pretest and posttest sample. There were 32 junior high school students participated in this study; divided into control group and experimental group. The result of the research data tested using Independent Samples t-Test showed the value of t= 3.023, (<0.05). It explained that the hypothesis is accepted, means the gratitude training can increase SoSB junior high school students significantly.